Goat Pleomorphic Adenoma Gene 1 (PLAG1): mRNA Expression, CNV Detection and Associations with Growth Traits - Qian Wang; Zhenyu Wei; Haijing Zhu; Chuanying Pan; Zhanerke Akhatayeva; Xiaoyue Song; Xianyong Lan (Animals, 2023)
The pleomorphic adenoma gene 1 (PLAG1) gene, as the major gene responsible for growth, plays a vital role in myogenesis. Meanwhile, the relationship between copy number variation (CNV) of this gene and growth traits in goats remains unclear. Therefore, this study investigated four aspects: bioinformatics analysis, mRNA expression (n = 6), CNV detection (n = 224), and association analysis. The findings indicated that the gene had a large number of conserved motifs, and the gene expression level was higher in fetal goats than in adult goats. Three CNV loci were selected from the database, among which CNV1 was located in the bidirectional promoter region and was associated with goat growth traits. CNV analysis showed that CNV2 and CNV3 of the PLAG1 gene were associated with growth traits such as body weight, heart girth, height at hip cross, and hip width (p < 0.05), with CNV1 loss genotype being the superior genotype, and CNV2 and CNV3 median and gain genotypes of being superior genotypes. This finding further confirms that the PLAG1 gene is the dominant gene for growth traits, which will serve as theoretical guidance for goat breeding.